THE CHARACTERISTICS OF MARINE PLANKTON AT AN INSHORE STATION IN THE GULF OF MANNAR NEAR MANDAPAM - Prasad, R Raghu (Indian Journal of Fisheries, 2016)
Study of the plankton of the inshore waters of the Gulf of Mannar wasstarted in 1950 as a part of the programme of work carried out at the CentralMarine Fisheries Research Station. As plankton forms directly or indirectlythe food of fishes the primary object of this investigation is to get a generalpicture of the changes in the total plankton concentration, as indicated byfluctuations in the net-plankton volume, as well as the plankton compositidnand its relation to local fisheries.